The Aesthetics of some Kasem Traditional Prayers - Umar Abdul-Hakim (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study examines the aesthetics of three Kasena traditional prayers performed in devotion to Kukula, a divinity revered by the Kasena of the Upper East Region of Ghana. These prayers are performed orally and have not received any literary study in Kasem; this study is therefore aimed at filling this gap by looking at the aesthetics in this prayers. Four different prayers were recorded and transcribed by the researcher; these prayers were collected from Kayᴐrᴐ, a village in the Kasena Nankana West District in the Upper East Region of Ghana. We define these prayer texts as being part of Kasem oral literature. The literary theory of structuralism is adopted for this study. The instruments I used in collecting the information for this study included, voice recorder, video recorder, while the researcher used active participatory method of observation and data elicitation in the data collection. The analysis reveals that the officiant in their performances of these prayers use native poetic devices such as; proverbs, rhetorical questions, metaphor, personification, oxymoron, synecdoche, symbolism, imagery and repetitions of varying degrees. They also use allusions, alliteration and assonance. The study of these prayers reveals that these performers have a mastery of many artistic devices native to Kasem. In conclusion the study clearly shows that even though the officiants of these traditional prayers are merely performing religious activities, they use literary language during their compositions, thus, making Kasena traditional prayer texts artistic compositions.